Completeness and timeliness of diphtheria-tetanus-pertussis, measles-mumps-rubella, and polio vaccines in young children with chronic health conditions: A systematic review. Issue 13 (22nd March 2019) - Walker, Emma J.; MacDonald, Noni E.; Islam, Nehal; Le Saux, Nicole; Top, Karina A.; Fell, Deshayne B.
Abstract: Objective: To systematically review literature on uptake and timeliness of diphtheria-tetanus-pertussis, measles-mumps-rubella, and/or polio-containing vaccines in infants who were born preterm, with a low birth weight, and/or with chronic health conditions that were diagnosed within the first 6 months of life. Methods: Using a standardized search strategy developed by a medical librarian, records were extracted from MEDLINE, Embase, Database of Abstracts of Reviews of Effects, and CINAHL up to May 8, 2018. Results: Out of the 1997 records that were screened, we identified 21 studies that met inclusion criteria. Eleven studies assessed vaccine coverage and/or timeliness in preterm infants, 6 in low birth weight infants, and 7 in children with chronic health conditions. Estimates of coverage in these populations were highly variable, ranging from 40% to 100% across the vaccines and population groups. Conclusions: There is a lack of studies reporting coverage and timeliness of routine immunizations in special populations of children. Policy implications: Our review suggests a need for improved surveillance of immunization status in special populations of infants, as well as a need for standardization of reporting practices.